Practice in Management and Entrepreneurship: Some Facts from the Bucharest University of Economic Studies - Eduard Gabriel CEPTUREANU; Sebastian Ion CEPTUREANU (Revista de Management Comparat International)
According to EU policy strategy aimed at youth, "Youth - Investing and Empowerment" youth is one of the most vulnerable groups in society, especially in the current economic and financial crisis and increasingly aging society, young people are a precious resource. The young generation is an ongoing resource reduction, it is estimated that 20% of the population that it is now projected to fall to 15% by 2050. While EU youth today enjoy numerous opportunities, they face difficult challenges, also, because many young people leave school and work or are at risk of poverty and social exclusion. This papers exhibit some interesting facts about the intensity of entrepreneurial spirit within the most important and prestigious economic university in Romania, The Bucharest Academy of Economic Studies. The aim of the research was to found out the basic portrait of the future entrepreneur graduating from our university and their main advantages and disadvantages related to their perception of Romania’s business environment.